The Relationship between Motivation and Learning Outcomes of Grade IV Elementary School Students: Hubungan Motivasi Dengan Hasil Belajar Siswa Kelas IV Sekolah Dasar - Jahrotul Faizah; Tri Linggo Wati (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the relationship of motivation to learning outcomes of fourth grade students at SDN Juwet Kenongo Porong Sidoarjo. This research uses quantitative research. The method used is ex post facto. The design used in this research is product moment correlation. The instrument used in the study was a questionnaire. The sample in this study were all fourth grade students at SDN Juwet Kenongo Porong Sidoarjo using a saturated sample. Data analysis techniques in this study used validity, reliability, and hypothesis testing. The results showed that motivation had a relationship with student learning outcomes.